2019
DOI: 10.3390/polym11121995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Single/Collective Use of Curing Agents on the Curing Behavior and Bond Strength of Soy Protein-Melamine-Urea-Formaldehyde (SMUF) Resin for Plywood Assembly

Abstract: Soybean protein hydrolysate, melamine, urea, and concentrated formaldehyde were used to synthesize an environmentally friendly soybean protein-melamine-urea-formaldehyde (SMUF) co-condensation resin. (NH4)2SO4, (NH4)2HPO4, (NH4)2HPO4 + (NH4)2SO4, (NH4)2HPO4 + (NH4)2S2O8, and (NH4)2HPO4 + (NH4)2SO4 + (NH4)2S2O8 were employed as curing agents for SMUF resin. The curing and thermal behaviors of the SMUF resin were investigated using differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Urea-formaldehyde resins, generated by the polycondensation of formaldehyde, urea, and other modifiers, are one of the most important members of thermosetting resins [1][2][3]. Due to their simple synthesis process, excellent thermal properties, low curing temperature, resistance to microorganism, low cost, and excellent mechanical properties, UF resins have been widely used as wood adhesives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urea-formaldehyde resins, generated by the polycondensation of formaldehyde, urea, and other modifiers, are one of the most important members of thermosetting resins [1][2][3]. Due to their simple synthesis process, excellent thermal properties, low curing temperature, resistance to microorganism, low cost, and excellent mechanical properties, UF resins have been widely used as wood adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, UF resins can be effectively catalyzed in practical production by inorganic acids or acidic salts such as ammonium chloride, ammonium sulfate, phosphoric acid, etc. [1,4]. For example, Li et al have investigated the effects of curing agents, including ammonium chloride and hexamethylenetetramine, on the properties and performance of the UF resin [4].…”
Section: Introductionmentioning
confidence: 99%
“…36 The peaks at 1655 and 814 cm À1 were assigned to C]O stretching and the triazine ring out-of-plane vibrations, respectively. 29 Further, the weak peak at 2960 cm À1 and the strong peak at 1003 cm À1 were assigned to stretching vibrations of -CH 2and bending vibrations of the C-O from hydroxymethyl groups (-CH 2 OH), respectively. 29,32 The results indicated that urea and melamine were successfully hydroxymethylated.…”
Section: Resultsmentioning
confidence: 99%
“…29 Further, the weak peak at 2960 cm À1 and the strong peak at 1003 cm À1 were assigned to stretching vibrations of -CH 2and bending vibrations of the C-O from hydroxymethyl groups (-CH 2 OH), respectively. 29,32 The results indicated that urea and melamine were successfully hydroxymethylated. Moreover, according to the GPC spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation